Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.7 The Chain Rule - 3.7 Exercises - Page 191: 34


$y' = -4cos(4cos (z))sin(z)$

Work Step by Step

$y = sin (4cos (z) )$ $y' = (sin (4cos (z) ))'$ The inner function is $g(z) = 4cos (z)$ and the outer function is $f(u) = sin(u)$ $f'(u) = cos(u)$ $y' = (sin (4cos (z)))' = cos(g(z))g'(z) = cos(4cos (z))\times -4sin(z) = -4cos(4cos (z))sin(z)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.